The role of seaports in the energy supplies markets: the case of wind energy in Texas. (20th March 2023) - Gharehgozli, Amir; Galvao, Cassia Bomer; Mileski, Joan P.; Swaney, Ryan
The seaport and the energy industry historically have shared strategic assets. Today, the use of renewable sources such as wind, solar and hydropower is increasing significantly. The USA recognises that energy sustainability requires the development of renewable sources. Texas ranks as the #1 State in the USA for wind energy generation. Ports are indispensable in the transportation of the wind energy generation components, as they are large and imported from outside the USA. Due to the logistics specialisation required to move these components, developing port terminals that can streamline and increase the throughput of wind energy paraphernalia are critical to the growth of wind energy. Thus, this research examines the logistic challenges involved in global transportation wind energy material/equipment as the trade for this equipment increases from abroad to the USA. Furthermore, we develop a comprehensive cost optimisation model which includes the cost of production and transportation of wind energy components through ports from suppliers to installation sites. We evaluate the model through a case study considering the energy production and generation matrix using the data from ports in Texas. Further, Texas is the only state in the country operating with an independent electrical grid.